Immigration Restrictions as Active Labor Market Policy: Evidence from the Mexican Bracero Exclusion - Michael A. Clemens; Ethan Gatewood Lewis; Hannah M. Postel (Institute of Labor Economics (IZA), 2017)
An important class of active labor market policy has received little rigorous impact evaluation: immigration barriers intended to improve the terms of employment for domestic workers by deliberately shrinking the workforce. Recent advances in the theory of endogenous technical change suggest that such policies could have limited or even perverse labor-market effects, but empirical tests are scarce. We study a natural experiment that excluded almost half a million Mexican 'bracero' seasonal agricultural workers from the United States, with the stated goal of raising wages and employment for domestic farm workers. We build a simple model to clarify how the labor-market effects of bracero exclusion depend on assumptions about production technology, and test it by collecting novel archival data on the bracero program that allow us to measure state-level exposure to exclusion for the first time. We cannot reject the hypothesis that bracero exclusion had no effect on U.S. agricultural wages or employment, and find that important mechanisms for this result include both adoption of less labor-intensive technologies and shifts in crop mix.
Keywords: J08; J38; F22; J61; 330; immigrant; immigration; displacement; visa; labor-market; employment; wage; farm; agriculture; natural experiment; United States; Mexico